Web application testing B - Ren, Si Qi (2015)
The objective of this project is to carry out software testing on web applications, both functional and performance test. The test includes user acceptance test, compatibility test, load test and stress test. The web application to be tested is Online Peer Ranking System developed on Linus-Apache-MySQL-PHP (LAMP). At the end of the project, we should be able to know whether the system has any functional defects and if it could perform errorless under extreme heavy load. Black-box testing is conducted on the system which does not require any prior knowledge of the programming technique of the system. Decision tables are used for test case generation for user acceptance test and change setting test. Automated testing tools are used for both functional and performance test. Selenium WebDriver, integrated with TestNG is used for functional test. Apache JMeter and JMeter Plugins are used for performance test analysis. In this project, the following web application tests are conducted.1) UAT (User Acceptance Test ) 2) Cross Browser Test 3) Load Test 4) Stress Test. The test result have concluded that there is no observable functional defects of the subject system. All proper prompt messages are displayed as expected and the system is compatible with three major browsers; IE, Firefox, and Chrome. Performance wise, the subject system is robust to be used under normal load of 150 user login and perform actions concurrently. Keeping all other variables unchanged, the system is robust until 300 user login concurrently, which is double of the expected maximum user. Therefore, we could conclude that the system is good to be used by end users.